THE CHARACTERIZATION OF GUAVA ECO ENZYME AND ITS CORRELATIONS TO NH3, PO4, AND pH REDUCTION IN WATER SAMPLES - Muhammad Haekal Bahari; Temmy Wikaningrum (Journal of Environmental Engineering and Waste Management, 2022)
Production of organic waste that is dominating waste generation becomes a problem for the environment. Eco enzyme is a solution made from brown sugar, water, and fermented fruit waste. Eco enzyme can become one of solution to reduce waste generation. Eco enzyme utilize organic waste recycling and brown sugar as the fermentor. This solution can be utilized into multipurpose cleaning liquids, eco enzyme also can reduce the wastewater contaminant, it can reduce effect of wastewater after dispose to the environment. This research has purpose on determines the characteristic of the guava eco enzyme and the correlation on the reduction of NH3, pH, and PO4 in water. The research results show that the guava eco enzyme is acidic with pH 3.36, it also containing 1.4 ppm of NH3, 11.2 ppm of PO4, and 116800 mg/l of COD. From the observation in the variation of time eco enzyme can reduce NH3 and PO4 also pH value. With 2% of guava eco enzyme concentration, it can reduce 27.5 % of NH3 with eight hours observation and 20% of PO4 contaminant in the water in 6 hours observation. From the analysis of guava eco enzyme, resulted that a higher concentration of an guava eco enzyme can reduce higher contaminant. With higher concentration of eco enzyme which 5%, 7%, and 10% it can reduce 28.3%, 30.1%, and 31% of NH3. From correlation analysis there is strong correlations between NH3 and pH reduction percentages with a concentration of eco enzyme added to the water.  A small amount of guava eco enzyme also effective in reducing the pH of the water. It can reduce until 50% of pH by 2.4% eco enzyme concentration. This finding may contribute as the baseline for further improvement of household wastewater pre-treatment.